2003
DOI: 10.1046/j.1471-0528.2003.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of ursodeoxycholic acid and S‐adenosyl‐l‐methionine in the treatment of gestational cholestasis

Abstract: Objective To compare the efficacy of S-adenosyl-L-methionine and ursodeoxycholic acid in improving serum biochemical abnormalities in gestational cholestasis. Design Randomised clinical trial.Setting University hospital.Population All women at <36 weeks of gestation with severe gestational cholestasis during June 1996 to December 2001. Methods Enrolled women were randomly assigned oral S-adenosyl-L-methionine 500 mg twice daily or oral ursodeoxycholic acid 300 mg twice daily until delivery. Main outcome measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
0
12

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 20 publications
2
51
0
12
Order By: Relevance
“…The efficacy of the glutathione precursor S-adenosylmethionine (SAMe) is controversial [86,87] . A controlled trial (46 patients) comparing SAMe with UDCA found that UDCA was significantly more effective at improving the concentration of serum bile acids and other liver biochemical tests, whereas both drugs equally reduced pruritus [88] . Another randomized placebo-controlled trial involving 32 patients showed the superiority of the combination of UDCA with SAMe over either drug alone for alleviating pruritus and improving liver tests [89] .…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…The efficacy of the glutathione precursor S-adenosylmethionine (SAMe) is controversial [86,87] . A controlled trial (46 patients) comparing SAMe with UDCA found that UDCA was significantly more effective at improving the concentration of serum bile acids and other liver biochemical tests, whereas both drugs equally reduced pruritus [88] . Another randomized placebo-controlled trial involving 32 patients showed the superiority of the combination of UDCA with SAMe over either drug alone for alleviating pruritus and improving liver tests [89] .…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Un seul cas de MFIU a été décrit au cours d'un traitement par AUDC [21]. Il existe à ce jour au moins sept études randomisées avec l'AUDC : quatre comparant l'AUDC avec le placebo [45][46][47][48], trois avec la S-adénosyl-méthionine (SAMe) [49][50][51] et une étude avec la cholestyramine [16] (Tableau 2). De plus, il existe une étude prospective non randomisée comparant l'AUDC à fortes doses (1500 à 2000 mg/j) à un groupe de malades non traitées [52].…”
Section: Traitement De La Cholestase L'acide Ursodéoxycholique (Delurunclassified
“…concentration sérique des acides biliaires dans le groupe traité par AUDC [16,[45][46][47][48][49][50][51][52]. Dans trois études randomisées comparant l'AUDC à un placebo, il a été montré que l'AUDC permettait de prolonger significativement le terme de la grossesse [45,47].…”
Section: Traitement De La Cholestase L'acide Ursodéoxycholique (Delurunclassified
“…Agents such as phenobarbital, anion exchangers, S-adenosyl methionine, and others have been tested but not introduced into clinical practice due to uncertain efficacy and/or intolerable side effects. [11][12][13] However, small studies with ursodeoxycholic acid (UDCA) and dexamethasone indicate that pharmacologic treatment may provide relief from pruritus and reduce serum bile acid and liver enzyme levels. UDCA has been tested in two randomized, placebo-controlled studies, with 8 patients in each group.…”
mentioning
confidence: 99%